2017
DOI: 10.18632/oncotarget.17436
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of soluble mesothelin in malignant pleural mesothelioma: a meta-analysis

Abstract: BackgroundSoluble mesothelin is beneficial to detect the progression and the treatment response of malignant pleural mesothelioma. However, the prognostic value of soluble mesothelin in malignant pleural mesothelioma remains unclear.MethodsHazard ratio with 95% CI was used to evaluate the prognostic value of soluble mesothelin and the effect of clinicopathological characteristics on the survival of malignant pleural mesothelioma.ResultsEight eligible studies involving 579 patients were selected for this meta-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 45 publications
0
29
0
2
Order By: Relevance
“…12,14 Several studies also investigated SMRP as a prognostic biomarker in MM. 18,[21][22][23] SMRP levels were markedly increased at disease progression. 21 In a meta-analysis, increased SMRP was associated with shorter overall survival and worse prognosis.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…12,14 Several studies also investigated SMRP as a prognostic biomarker in MM. 18,[21][22][23] SMRP levels were markedly increased at disease progression. 21 In a meta-analysis, increased SMRP was associated with shorter overall survival and worse prognosis.…”
Section: Introductionmentioning
confidence: 94%
“…It is involved in important cellular processes, including cell adhesion, proliferation, invasion, and epithelial-to-mesenchymal transition. 18,19 Mesothelin is a glycophosphatidylinositol-linked membrane protein, but it also has three isoforms that are present in the circulation. 12,15,20 Enzyme-linked immunosorbent assay (ELISA) can detect different isoforms, usually referred to as soluble mesothelin related peptides (SMRP).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most investigated biomarkers in MM is mesothelin, a circulating form of a glycoprotein attached to the cell surface, that is considered to have a role in cell adhesion, proliferation, invasion, and possibly in cell-to-cell signalling. Mesothelin is highly expressed in MM as well as in several other cancers [14][15][16][17][18]. It exists in different forms that can be detected in serum in the form of soluble mesothelinrelated peptides (SMRP) by enzyme-linked immunosorbent assay (ELISA) using monoclonal antibody techniques [19].Many studies have investigated mesothelin as a possible tumour biomarker for diagnosing MM, evaluating response to treatment, as well as for detecting the progression of this malignoma [16,[20][21][22][23][24][25][26].…”
Section: Mesothelinmentioning
confidence: 99%
“…Its prognostic value has been strongly debated: many following studies confirmed this association (13-15) but others did not endorse serum mesothelin prognostic significance (26,87). While a recent meta-analysis performed on 579 MPM patients further corroborates the inverse association of serum SMRP concentration with the OS (16). The mixed results observed are due to the small samples size and to the heterogeneity of the treatment among the studies and lead to the necessity of further investigations.…”
Section: Clinical Implications Of Overexpressed Genes In Mpmmentioning
confidence: 99%